Growth of Leiognathus splendens (Cuvier, 1829) based on daily otolith rings validated through length frequency analysis - Penaflor, Grace C. (College of Fisheries, University of the Philippines in the Visayas, 1987)
Sagittae of Leiognathus splendens were extracted and examined for this study. Of the 980 pairs of otoliths examined, only 35 otoliths were found to have clear readable rings. These rings were counted and incrment counts were used to determine the growth of L. splendens. Growth parameters were estimated from the otolith increment data using ETAL I and the growth equation Lt = 14.0 (1 - e -1.083 (t + 0..047) was derived. The age data was validated by comparing growth curves obtained from the gae dta with growth curves derived from lenght frequency data using the data of Donaldo (1979) from Manial Bay. Validation was done using ELEFAN V. The age data alone yielded a K = 1.083, length data generated a K = 0.857 and a combined analysis of the two data sets resulted in a K = 0.86, implying similar shapes in theigrowth curves. A comparison of these values with similar growth parameter estimates on L. splendens showed that the K values are quite close to each other. These results establish the validity that the otoliths of Leiognathus splendens deposit an average of one increment per day.